On winning the "lottery": psychological preparation for football penalty shoot-outs - Wood, G.; Jordet, G.; Wilson, M. R. (Journal of Sports Sciences, 2015)
The outcome of penalty shoot-outs is often referred to as a "lottery", suggesting that luck, rather than the skill level of the player, predetermines outcome success. Throughout this article, we hope to show why such attitudes towards physical and psychological preparation can increase anxiety, diminish perceptions of control and negatively affect the behaviour and subsequent performance of penalty takers. From the synthesis of this evidence, we provide task-specific recommendations that are structured around the dynamic nature of emotions that players are likely to experience during each phase of the shoot-out and which can be implemented or adapted to suit the individual needs of the player. These recommendations are designed to provide a framework to help applied professionals to optimise the psychological preparation for this scenario with the overall aim of helping players to (re)gain control of this situation.